2017
DOI: 10.1002/slct.201701955
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid‐Encapsulated Zeolite Catalysts for the Conversion of Glucose to 5‐Hydroxymethylfurfural

Abstract: Ionic Liquid (1‐Butyl‐3‐methylimidazolium Bromide ([BMIM]Br) or Choline Chloride (ChCl)) encapsulated zeolites (HY and H‐MOR) have been synthesized by ship‐in‐a‐bottle strategy and tested for selective conversion of glucose to 5‐Hydroxymethylfurfural (HMF). Nitrogen sorption analysis showed that the surface area and total pore volume decreased and average pore size increased significantly when the zeolites are encapsulated with ionic liquids. The major effect was found to be on the microporosity whereas the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
(37 reference statements)
3
5
0
Order By: Relevance
“…The surface area of CaX had reduced from 343 to 28 m 2 /g, upon anchoring the thin ionic liquid film. The decreases in the BET surface areas of IL/CaX were attributed to the immobilization of ionic liquid on porous CaX, resulting in the block of micropores and decrease of surface areas [27]. The structural properties of the supported ionic liquid on zeolite agreed with the reported values in Reference [28].…”
Section: Catalytic Characterizationsupporting
confidence: 83%
See 1 more Smart Citation
“…The surface area of CaX had reduced from 343 to 28 m 2 /g, upon anchoring the thin ionic liquid film. The decreases in the BET surface areas of IL/CaX were attributed to the immobilization of ionic liquid on porous CaX, resulting in the block of micropores and decrease of surface areas [27]. The structural properties of the supported ionic liquid on zeolite agreed with the reported values in Reference [28].…”
Section: Catalytic Characterizationsupporting
confidence: 83%
“…However, the relative intensity of (111) peak was lower than that of CaX. This could be attributed to the disordering of the porous structure and variation the electron density (especially for the major peak at 2θ = 6.1 • ), due to immobilization of an ionic liquid layer onto zeolite [27,28]. These results agreed well with the SEM analyses.…”
Section: Catalytic Characterizationsupporting
confidence: 81%
“…Further, in our previous works, we explored the routes for the production of LA/HMF from the biomass, cellulose, or C6 sugars using stable hierarchical/functionalized zeolite catalysts. [ 34–38 ] The integration of the process reported in the present study with our previously reported C6 routes for LA production allows the complete utilization of the C5 and C6 parts of the lignocellulosic biomass.…”
Section: Resultsmentioning
confidence: 86%
“…U.S. Energy Department recognized levulinic acid among the platform chemicals. 144 Several heterogeneous catalysts such as HZSM-5, 145 HY zeolite, 146 ionic liquid encapsulated zeolites, 147 Sn-beta, 148 Amberlyst 70, 149 SAC13, ZrO 2 , 150 and niobium oxides 151 have been examined towards the conversion of cellulose to levulinic acid. But, these catalysts are suffering from a few drawbacks for instance low yields, low conversion, 152 reaction times are longer, 153 need of costly and harmful solvents, as well as deactivation caused by the formation of humins.…”
Section: Methodsmentioning
confidence: 99%